Characteristics of School Administrators in the 21st Century under the Office of UdonThani Primary Educational Service Area 4 - Srimungban, Adisorn (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were to study the characteristics of school administrators in the 21st century under the Office of Udon Thani Primary Educational Service Area 4, The sample used in the research consisted of 308 teachers under the Office of Udon Thani Primary Educational Service Area 4 in the academic year 2019. The research instrument was a five-rating scale. The statistics used for data analysis are percentage, mean, standard deviation. One-way Analysis of Variance and test the difference of the average value by pair with the Scheffe method. The research found that : 1. The opinions about the characteristics of school administrators in the 21st century under the Office of Udon Thani Primary Educational Service Area 4 were at a high level. 2. Comparison of characteristics of school administrators in the 21st century under the Office of Udon Thani Primary Educational Service Area 4 as according to teachers' opinions. Classified by educational qualifications and work experience, found that there are statistically significant differences .05 and classified by school size overall no difference. 3. Guidelines for development of characteristics of school administrators in the last century. Under the Office of Udon Thani Educational Service Area 4, it was found that school administrators should have a wide vision to keep up with the introduce changes in the present time. Have a clear policy schools to participate in the formulation of strategies with the community. Clearly define the roles and responsibilities, systematically with the ability of personnel not too flexible or too strict there is support to support classroom management to facilitate learning. Use technology to teach, have mercy, sacrifice, morality, and ethics in the administration of the organization for effective development.